By all means necessary : how China's resource quest is changing the world - Economy, Elizabeth, 1962-; Levi, Michael A. (Oxford University Press, 2014)
"In the past thirty years, China has transformed from an impoverished country where peasants comprised the largest portion of the populace, to an economic power with an expanding middle class and more megacities than anywhere else on earth. Like every other major power in modern history, China is looking outward to find the massive quantities of resources needed to maintain its economic expansion; it is now engaged in a far flung quest around the world for fuel, ores, water, and land for farming. Chinese traders and investors buy commodities, with consequences for economies, people, and the environment around the world. Meanwhile the Chinese military aspires to secures sea lanes, and Chinese diplomats struggle to protect the country's interests abroad. In By All Means Necessary, Elizabeth Economy and Michael Levi explore the unrivaled expansion of the Chinese economy and what has been required to sustain this meteoric growth. Clear, authoritative, and provocative, By All Means Necessary is a sweeping account of where China's pursuit of raw materials may take the country in the coming years and what the consequences will be -- not just for China, but for the whole world"--